2022
DOI: 10.1177/10870547221075844
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Mental Health and Substance Use on Suicidal Behavior Among Undergraduate Students With ADHD

Abstract: Objective: To evaluate the prevalence of suicidal ideation (SI), plans and attempts, and non-suicidal self-injury (NSSI) among students with attention deficit hyperactivity disorder (ADHD). Furthermore, we explored the mediating effects of depression, anxiety, alcohol and substance use on the association between ADHD and suicidal behaviors and NSSI. Method: Participants were first-year undergraduate students ( n = 1,829) recruited as part of the World Mental Health International College Student Initiative. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…However, these traits have been found to mainly predict suicide attempts and to a much lesser extent, suicidal ideation [ 86 ]. Nevertheless, some studies have observed direct associations of ADHD with suicidality after controlling for comorbid psychiatric disorders [ 87 89 ]. To the best of our knowledge, none of the previous studies has tested the mediating effect of PLEs in the association between ADHD symptoms and suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…However, these traits have been found to mainly predict suicide attempts and to a much lesser extent, suicidal ideation [ 86 ]. Nevertheless, some studies have observed direct associations of ADHD with suicidality after controlling for comorbid psychiatric disorders [ 87 89 ]. To the best of our knowledge, none of the previous studies has tested the mediating effect of PLEs in the association between ADHD symptoms and suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Evans et al (2022) found that there may be a correlation between ADHD symptoms and NSSI in veterans. Brown et al (2022) found that the incidence of suicide and NSSI among college students with ADHD was significantly higher than that of college students without ADHD. Their conclusions identified specific risk predictors for students with ADHD.…”
Section: Introductionmentioning
confidence: 91%
“…With similar findings corroborated in ADHD samples, 14 this heightened risk in autistic people with ADHD is importantly independent of psychiatric conditions like anxiety, depression and substance abuse, 13 which are also more common in this cohort 15,16 and a major correlate and risk factor for suicidality, in and of themselves, in both autistic and ADHD populations. 2,17,18 Similarly, a number of studies report an association between ADHD and suicidality 14,[19][20][21] which is separate from these confounds and seemingly reflects something about living in the world as an individual with ADHD. 22 These concerning findings highlight the need to examine the role of co-occurring ADHD in autistic suicidality and to identify the mechanisms through which these individuals might be at greater risk.…”
Section: Introductionmentioning
confidence: 99%